-2(n-14)=-10

Simple and best practice solution for -2(n-14)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(n-14)=-10 equation:


Simplifying
-2(n + -14) = -10

Reorder the terms:
-2(-14 + n) = -10
(-14 * -2 + n * -2) = -10
(28 + -2n) = -10

Solving
28 + -2n = -10

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + -2n = -10 + -28

Combine like terms: 28 + -28 = 0
0 + -2n = -10 + -28
-2n = -10 + -28

Combine like terms: -10 + -28 = -38
-2n = -38

Divide each side by '-2'.
n = 19

Simplifying
n = 19

See similar equations:

| 20e^4t=11e^9t | | -6=2.5w-5 | | 16.3y=-2(9.8y+18.97)-18.3y | | 23+6c=95 | | 16+n+20=-17n-18 | | 2(s+1)-2=4 | | 15+b=25 | | 6(2p-2)=-24 | | 9=3(f+2) | | 3b+20=5b-12 | | 5g=6g+10 | | 75=4(-6n-5) | | -12-8t=52 | | 18e^2t=13e^7t | | 3(w-19)-14=-14 | | -5+12x=67 | | -14.07-18.9m=14.76-17.1m-12.99 | | 4(f-19)=-16 | | 3f=4f+10 | | X-1+5x-3+5x-3= | | 6+6r=18 | | 9+9m=-9+6m+5m | | -16=30x+15x^2 | | 6x-15x=18 | | -2x-39=-6x+29 | | 6a+4a-3a= | | 63x^8=0 | | 4k+ar=r-7y | | -3(t-5)+5t=7t-4 | | X^2+6x-1=7x-9 | | -4.19+11.5c=10c-0.87+1.7c | | 6x+3x-6=10x+5 |

Equations solver categories